Epidemiological study of herpes zoster in a tertiary care hospital - Baghel, Nekram; Awasthi, Sankalp; Kumar, Sweta S. (International Journal of Research in Medical Sciences, 2017)
Background: Herpes Zoster, which presents as a localized, painful cutaneous eruption is a common clinical problem, caused by reactivation of latent Varicella Zoster Virus (VZV) and is usually self- limiting in healthy adults. In this era of HIV infection, HIV seropositive patients are at increased risk of severe or disseminated cutaneous or visceral involvement. Aim was to analyse the clinical pattern and epidemiological factors of Herpes Zoster and to know the HIV prevalence among patients with Herpes Zoster. Methods: A total of 110 patients with Herpes Zoster attending dermatology department at Uttar Pradesh university of medical sciences (UPUMS), Saifai, Etawah, India from a period of July 2015 to July 2017 were included in the study. Results: Out of 110 patients, 79 were males 31 were females. Age group varied from 8-80 years. Most common dermatomes involved were thoracic followed by ophthalmic division of trigeminal nerve. 33.6% of patients showed HIV seropositivity. Most commonly observed complication was post herpetic neuralgia which was encountered in 36% of the patients and most of these patients were above the age of 60 years. Post herpetic neuralgia was more commonly seen in seropositive individuals as compared to seronegative individuals. Conclusions: Disseminated zoster and multi-dermatomal involvement were encountered in immuno-compromised individuals. Post herpetic neuralgia was seen in elderly patients, especially in case of ophthalmic zoster.